The Effectiveness of Group Counseling Acceptance and Commitment Therapy to Reduce Students’ Academic Burnout - Kalsum, Ummu; Eddy Wibowo, Mungin; Japar, Muhammad (Universitas Negeri Semarang, 2022)
Academic burnout is a kind of problem experienced by students. To deal with this, acceptance and commitment therapy group counseling was assumed to be the solution. Hence, this study attempted to examine the effectiveness of acceptance and commitment therapy group counseling to reduce students’ academic burnout. It used multiple group pretest-posttest design and involved 14 students grouped into two chosen using purposive sampling technique based on high level of academic burnout. The students’ data were collected using Maslach Burnout Inventory-Students Survey (MBI-SS) which has been adopted to Indonesian and obtained cornbach alpha coefficient of 0.85. Based on mixed ANOVA test, the acceptance and commitment therapy grup counseling was effective to reduce the students’ academic burnout. Further implications and limitations of this study are discussed in the discussion chapter